Numerical studies of temperature changes in adult and paediatric patients in brain magnetic resonance imaging - Subaar, Christiana (University of Cape Coast, 2019)
Magnetic Resonance Imaging (MRI) of the brain has seen a rising clinical request during diagnosis. The ohmic heating of tissue results in rising human temperature during MRI. This may be as a result of the unintentional heating which seems to be an under-appreciated risk especially of high-field-strength MRI. This study modelled Penne‘s bio-heat equation and used Matlab programming language to predict in-vivo power deposition in brain tissues during brain MRI of Radiofrequency (RF) above 100 kHz. Experimental thermal dosimetry was carried out on 114 patients. These patients were referred for (head) brain MRI at field strength of 0.3 tesla and 1.5 tesla at the same scanning protocols of specific absorption rate (SAR) of 3.2 W/kg. The experimental results showed that the highest change in temperature of 0.3 tesla is 1.2 °C and 1.5 tesla is 1.9 °C. The average change confirmed that the temperature distributions during MRI do not correlate well with SAR limit but rather showed a positive correlation with patients‘ body mass index, scan duration and the field strength. The lowest temperature during MRI from the simulated results was 37.5 °C and the highest temperature was 42.5 °C during brain scan of duration less than sixty minutes; this revealed that brain temperature increased as scan duration increased. The highest estimated brain temperature during brain MRI of the study was 43 °C and this depicted brain hyperthermia since the temperature value was above 41 °C. This might contribute to the causes of profuse localize sweating of some patients during MRI in the acceptable ambient MRI environment. It is, therefore, recommended that continuous temperature monitoring during MRI scan should be the most paramount, particularly if the scan durations are prolonged
xvii, 145p:, ill
Keywords: Brain Hyperthermia Imaging Magnetic resonance Patients Temperature